RELIGIOUS GUIDANCE MODEL TO DEVELOP STUDENT'S HONESTY CHARACTER - Neng Gustini, - (2022)
Neng Gustini, Religious Guidance Model to Develop Student's Honesty Character. Dissertation Supervised by Prof. Dr. H. Juntikan Nurihsan, M.Pd. (promoter), Prof. Syamsu Yusuf LN, M.Pd. (co-promoter), and Dr. Nandang Budiman, M.Pd., (promoter member). Post Graduate Program of Guidance and Counseling of the Indonesian University of Education. Bandung The phenomenon of academic dishonesty is still entrenched among students. Academic dishonesty behavior among students will trigger acts of corruption in their future working environment. Thus, it is important to develop the honesty character of students. The purpose of this study was to develop religious guidance model in developing the honesty character of students. This study uses a mixed method with an embedded concuren design. The instruments used in this study were questionnaires, observations and interviews. The research subjects were students of the Bachelor Program of Islamic Education Management, Faculty of Education and Teacher Training at UIN Sunan Gunung Djati Bandung. The results of the research are: 1) The honesty character profile of the students generally is categorized in honesty, but it is still found dishonesty in each aspect/dimension. This honesty character profile is used as initial information in the formulation of religious guidance models to develop students' honesty character; 2) The formulation of the religious guidance model to develop the honesty character of students includes several components, namely: (a) rationale, (b) key concepts and basic assumptions, (c) objectives, (d) definitions, (e) the domain of Guidance, covering: competency standards, competencies and indicators, intervention targets, forms of intervention and principles in Religious Guidance, (f) stages of model implementation, (g) functions and responsibilities of counselors in the process of religious guidance, (h) ) content and implementation of interventions, and (i) evaluation and indicators of success; 3) the model of religious guidance provides is properly implemented in developing the honesty character of students, marked by significant changes in the experimental group in each aspect, both aspects of the heart, oral, determination, and deed. This religious guidance model can be used as an alternative practical operational guide for counselors, education practicioner and stakeholders in developing the character and potential of students in higher education. Keywords: Religious Guidance, Honesty Character